Editorial (American Journal of Islam and Society, 2005)
This issue coincides with several momentous events and trends in the world atlarge and Muslim nations. The heads or top representatives of the 57 Muslimmajoritynations have held an extraordinary meeting at Makkah under theOrganization of Islamic Conferences’ (OIC) aegis. A major goal is to reactivateand empower the OIC so that it can actively help the ummah deal with itshuge opportunities and challenges. Several salient issues were stressed: theneed for closer interaction, collaboration, and internal reform leading to apeaceful, pluralistic, and moderate disposition of Islam and Muslims.Muslim nations are trying to address their internal weaknesses and buildupon their strengths. In terms of human and material resources, the Muslimworld is composed of three kinds of countries: those with large populationsand poor economies, small populations and rich economies, and with bothfairly large populations backed by rich economic resources. They seem tobelieve that Iraq and Iran, the very backbone of the third category, are currentlytargeted for long-term occupation. They are exploring how to compensatefor one another’s drawbacks and reinforcing their assets.The OIC declaration, hailed as a historic turning point, stresses thatMuslims take responsibility for their present plight and stop blaming others.In addition, the organization will be renamed, get a new charter, and be runby mandatory contributions from member nations. It will also feature conflict-resolution and consensus-building mechanisms to resolve both minorand major conflicts, such as Palestine and Kashmir. The ummah and theworld now wait to see whether such statements are more than rhetoric.Concurrently, there is an increasing awareness of the futility of cardinaldirectionalconflicts and the “clash of civilizations” between the West andthe East, or between the North and the South. Ever more Muslim and otherintellectuals realize that the real confrontation is between powerful globalforces of greed and exploitative profiteering on the one hand, and people ofcandor, conscience, and moral orientation on the other. Among the individualsand organizations in the latter camp, there is growing realization of theneed for societal reform toward pluralism, learning from each other, collectiveand consultative decision making, basic freedoms for all, peace withjustice, and institution building that is compatible with the speed, complexity,and magnitude of the emerging globalized world ...